Political Economization vs Economic Politicization: A Comparative Study of Park Chung Hee's and Soeharto's Leadership in Promoting Economic Development - Frederica, Wynne (Business and Investment Review, 2025)
This study aims to examine the differences in political-economic strategies between Park Chung Hee in South Korea and Soeharto in Indonesia, with a particular focus on how authoritarian leadership and discriminatory economic policies influenced the direction and outcomes of national development. It explores how Park’s approach, centered on economic discrimination, meritocratic industrial policies, and corporate-led growth fundamentally differed from Soeharto’s strategy, which relied heavily on political patronage and the politicization of economic policy. This research adopts a qualitative descriptive approach using library research methods, by reviewing relevant academic journals and scholarly publications. The analysis is conducted by interpreting key themes in each leader’s development policies, particularly concerning the role of the state in creating economic incentives and shaping institutional structures that either promoted or hindered economic growth. Economic development remains one of the most critical challenges in postcolonial developing countries. This study compares two authoritarian regimes Park Chung Hee’s South Korea and Soeharto’s Indonesia. Both of which adopted state-led development models in the postcolonial era. Although both leaders shared similar institutional frameworks, military backgrounds, and centralized governance, their economic outcomes diverged significantly. Park’s leadership exemplified the “economization of politics,” where state power was used to enforce meritocracy, promote industrial performance, and discipline markets. South Korea achieved robust export-led industrialization and institutionalized economic meritocracy through support for chaebols and long-term planning. In contrast, Soeharto’s regime reflected “economic politicization,” wherein state resources were distributed based on political loyalty rather than performance. This led to structural fragility, inequality, and eventual collapse during the 1997 Asian Financial Crisis. Using a qualitative descriptive approach based on literature review, the study finds that authoritarian development success depends less on the degree of state control and more on the quality of governance, institutional discipline, and commitment to performance-based policies.